‘A lack of cultural understanding and sometimes interest’: Towards half a century of anti-racist policy, practice and strategy within probation - Wainwright, John (Probation journal, 2024)
In 2021, HM Inspectorate of Probation published a long awaited and highly critical report – Race equality in probation: the experience of black, Asian and minority ethnic probation service users and staff. The inspection upon which it was based was conducted in the Autumn of 2020 and was therefore set against the background of the death of George Floyd in the United States, and the rise of the Black Lives Matter movement worldwide. The Black Lives Matter (BLM) movement laid down a challenge on many levels, stating that black, Asian and minority ethnic people must be accepted and respected as equal citizens and nowhere is this more urgently needed than within the operation of the criminal justice system. However, its follow up report (HM Inspectorate of Probation 2023) reported being disappointed in the lack of progress made by the Probation Service in addressing the issues raised in its earlier report. The article seeks to move beyond the conclusions and recommendations of the Inspection report using the lens of Critical Race Theory to engage in a discussion of systemic racism in society. To do this we have used three levels of analysis – macro, meso and micro – to situate contemporary probation within the wider structures of a post-colonial society.